The Relationship Wound Grade and Neuropathy Status With Anxiety in Diabetic Foot Wound Patients - Hanafi, Hanafi; Ainun Najib Febrya Rahman2; Devi Harmita; Haryati Septiani; Ledy Ervita; Wulida Litaqia (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Background. Microvascular complications in diabetes mellitus patients often occur in the eyes (diabetic retinopathy) and diabetic neuropathy which will cause numbness in the extremities, while macrovascular complications can occur in coronary artery blood vessels in the heart, disorders of large blood vessels in the feet which will increase the risk of necrosis in the extremities Objective. The purpose of this study was to determine whether the relationship between Wound Grade and Neuropathy Status to the level of anxiety in patients with diabetic foot wounds Method. This type of research is descriptive analytical with a cross-sectional approach. Cross-sectional research with a sample size of 30, the sampling technique used by researchers was purposive sampling, the instruments in this study were observation sheets and Anxiety Inventory (S-AI) Form y Results. The results of the study obtained that there was no relationship between wound grade and anxiety levels in patients with diabetic foot wounds p-value 0.691> 0.05 and there was no relationship between neuropathy status and anxiety levels in patients with diabetic foot wounds p-value 0.248> 0.05 Conclusion. There was no correlation between wound grade and neuropathy status and anxiety levels in patients with diabetic foot ulcers